2022
DOI: 10.1039/d1dt04055c
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and electrochemical performance of nanowire-shaped Na3Mn2−xFex(P2O7)(PO4) for sodium-ion and lithium-ion batteries

Abstract: A series of Fe-doped Na3Mn2-xFex(P2O7)(PO4) (x = 0.0, 0.2, 0.4) (abbreviated as NMFP-0/NMFP-0.2/NMFP-0.4) compounds have been successfully prepared by using sol-gel method. The Rietveld refinement results indicate that single-phase Na3Mn2-xFex(P2O7)(PO4)...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Optimally, acceptable results can be obtained when the Mn/Fe ratio is 1:1 (Figure 8e) [78] . Moreover, these resulting binary phases follow the same single-phase reaction mechanism as Na 3 Mn 2 PO 4 P 2 O 7 [78,150] . For Na 2+2z Mn 2−z (SO 4 ) 3−x (SeO 4 ) x using monoclinic C2/c alluaudite-type structure, it can be regarded as a derivative obtained by partial substitution of SO 4 2− in Na 2 Mn 2 (SO 4 ) 3 with SeO 4 2− .…”
Section: Mixed Polyanionsmentioning
confidence: 91%
See 3 more Smart Citations
“…Optimally, acceptable results can be obtained when the Mn/Fe ratio is 1:1 (Figure 8e) [78] . Moreover, these resulting binary phases follow the same single-phase reaction mechanism as Na 3 Mn 2 PO 4 P 2 O 7 [78,150] . For Na 2+2z Mn 2−z (SO 4 ) 3−x (SeO 4 ) x using monoclinic C2/c alluaudite-type structure, it can be regarded as a derivative obtained by partial substitution of SO 4 2− in Na 2 Mn 2 (SO 4 ) 3 with SeO 4 2− .…”
Section: Mixed Polyanionsmentioning
confidence: 91%
“…Such electrode materials usually contain two or more polyanionic units, and the pairing of different anion groups can broaden the structural and redox potential diversity. For Mn-based materials, Na 3 MnPO 4 CO 3 [79,[140][141][142][143][144][145][146] , Na 4 Mn 3−x M x (PO 4 ) 2 P 2 O 7 (M is one or more of Fe, Co and Ni, 0 ≤ x < 3) [70][71][72][73][74][75][147][148][149] , Na 3 Mn 2−x Fe x PO 4 P 2 O 7 (0 ≤ x < 2) [76][77][78]150] , and Na 2+2z Mn 2−z (SO 4 ) 3−x (SeO 4 ) x [151] have been reported so far.…”
Section: Mixed Polyanionsmentioning
confidence: 99%
See 2 more Smart Citations
“…The low cost, high stability, and wide distribution of feedstock costs offered by sodium-ion batteries (SIBs) make them well-suited for fulfilling the demands of large-scale electrochemical energy storage systems. However, SIBs still have great challenges; despite having the same working principle as lithium-ion batteries (LIBs), they are limited by the ionic radius (Na + : 1.02 Å; Li + : 0.76 Å), which leads to poor de-embedding capability. Therefore, there is a need to develop more suitable electrode materials to fulfill large-scale storage requirements. In recent years, there has been a progression in sodium-ion cathode materials, with the emergence of various materials including transition-metal oxides, polyanion materials, and Prussian analogues. Iron-based polyanion materials with low raw material cost, high thermal stability, and environmental friendliness have gained a lot of attention for their advantages. Na 4 Fe 3 (PO 4 ) 2 P 2 O 7 (NFPP, theoretical capacity: 129 mA h g –1 ) was connected by combining [PO 4 ] and [P 2 O 7 ] groups with [FeO 6 ] octahedra, based on the redox Fe 2+ /Fe 3+ (average working voltage: 3.1 V), to realize the de-embedding of Na + in the cathode. Kim et al reported NFPP as a sodium-ion cathode material with a high reversible capacity of 113.5 mA h g –1 , marking the first discovery of such quality.…”
Section: Introductionmentioning
confidence: 99%